The Scale Effect of Investments and Tax Incomes intended to Public Sector Borrowing Requirement in Last Period: Turkish Case: JEL Codes: H23, H30, H63 - Özker, Niyazi (Archives of Business Research, 2020)
In this study, we attempt to put forth the structural dynamics in which the recent changes in the Public Sector Borrowing Requirement, which is an important phenomenon of the public sector, are related. We consider important that the public sector financial balances are affected by many sub-dynamics considering it is important to better understand the impact level of total investment expenditures and tax revenues in the process of changes in the Public Sector Borrowing Requirement (PSBR). However, it is also meaningful to question the changes in the borrowing requirement in the other macro dynamics that constitute the effect level in the process. Therefore, values ​​such as percentage changes in export limits, consumer confidence index and consumption investments in foreign markets were also included in our study. In this study, it was tried to determine the scale effect of the findings within the framework of an econometric model and the results were found to be meaningful as a result of the current interpretation from a financial economics perspective.